Professional learning communities in secondary schools and improvement of learning in challenging contexts - Olmo-Extremera, Marta; Domingo Segovia, Jesús; Khalil, Mohammad; De La Hoz Ruíz, Javier (Frontiers in Education, 2025)
Ensuring learning for all and by all in urban schools is a major challenge. It is therefore necessary to rethink schools and teacher performance to respond adequately to these challenges, especially in secondary education. In this respect, the extended professional learning communities model may be a viable alternative. This article presents data from the study of three secondary schools working to improve their educational outcomes. We adopt a case study methodology with an intrinsic, ethnographic, and autobiographical perspective to contextualize and understand the topic under study. The results reveal the degree of presence and development—at different levels of depth—of the dimensions that define an extended professional learning community. In these cases, they value the growth of their social and professional capital, with a sense of community, while weaving collaborative networks inside and outside the school around a shared purpose, i.e., liberating learning and ensuring learning for all. We conclude that the key conditions for achieving this goal are relational trust, professional interrelationship, co-responsibility, and clear shared leadership for learning, guided by the environment and underpinned by principles of care and social justice.